Environmental hepatitis E virus detection supported by serological evidence in the northwest of Argentina - Pisano, María Belén (2018)
Hepatitis E virus (HEV) is an emergent cause of acute hepatitis worldwide. Water contamination is a possible source of viral infection. In South America, particularly in Argentina, little is known about environmental HEV circulation, including recreational water. The aim of this work was to provide evidence of current environmental and human circulation of HEV in northern Argentina. Methods: Molecular detection of HEV in water samples from the Arias-Arenales River in the city of Salta by nested polymerase chain reaction (ORF2 region) and anti-HEV immunoglobulin G (IgG) and IgM detection in the general population by enzyme-linked immunosorbent assay was carried out. Results: HEV RNA was detected in 1.6% (3/189) of the environmental samples. All sequences belonged to HEV genotype 3 and were very similar to those previously detected in the country. The prevalence of IgG anti-HEV was 9% (13/143) and three samples were positive for specific IgM. Circulation of HEV in the northwest of Argentina was demonstrated for the first time, showing viral presence in environmental samples and infections in people who attended health care centres for routine control. These findings show that recreational waters are a possible source of virus and highlight the need to carry out HEV detection when a case of hepatitis occurs.